Erosive Wear of Dual Phase Steels Containing Different Amount of Martensite - Verma P.; Tyagi R.; Mohan S. (My University, 2025)
The present investigation is aimed at revealing the effect of martensite content and impingement angle on the erosive wear of dual phase (DP) steels developed via intercritical annealing (ICA) heat treatment by conducting erosion tests using air jet erosion tester at different angles of impact at a constant velocity of 90 m/s, using alumina (Al2O3) as the erodent. DP steels having four different martensite volume fractions (MVF) 0.39, 0.50, 0.65 and 0.79 were developed by holding normalized steel for different intercritical holding times, and their erosion behavior was examined at 15, 45, 70, and 90° angles of impingement. Normalized (N) steel was used as reference material for comparative purpose. The results indicate that steady state erosion rate decreases with increasing angle of impact for N steel as well as DP steels. However, DP steels showed a significantly reduced erosion rate in comparison with N steel reflecting the role of microstructure and consequent increase in hardness. Steady state erosion rate also decreased with increasing martensite content from 39 to 79%, and DP4 steel containing 79% martensite showed the best performance in terms of erosion resistance. The mechanism of material removal changed from micro-ploughing to crater formation with the increase in the angle of impingement. Micro-ploughing, lip formation, and embedded chips were identified as the operative erosion mechanisms for N steel, whereas ploughing, craters and cracks formation were the operative erosion mechanisms for DP steels. © 2022, ASM International.